The persistence and nature of the labor reallocation shock during the COVID-19 crisis - Mathieu P. A. Steijn (Tinbergen Institute, 2024)
The COVID-19 crisis may have widely and permanently altered the labor market through the demand for skills. Crises tend to accelerate technological change. Previous recent crises were characterized by an acceleration of automation, which generally led to a decrease in middle-income jobs with routine skills, known as job polarization. This study finds that the COVID-19 pandemic, which is characterized by an acceleration of digitization, has led to a unique, large, and relatively persistent labor reallocation shock. Labor market dynamics in the Netherlands reveal an unprecedentedly large rise in high-income jobs and an unprecedentedly large drop in low-income jobs. These dynamics are strongly associated with a previously virtually irrelevant job characteristic in occupations, namely, the ability to work from home, and not the manual, routine, or abstract thinking skill content of jobs that had strong explanatory power in previous recent crises. This suggests an acceleration of the importance of digital skills rather than abstract thinking skills. Post-pandemic trends up to 2023Q4 indicate that there is a recovery in the types of jobs (relatively) lost but that the reallocation shock is quite persistent in the type of jobs gained. Further evidence of a persistent change in the demand for (digital) skills is found in results on job mobility. These show that the pandemic is associated with a persistent improved probability in obtaining a high-income job for persons with lower levels of education but relatively reduced chances for older persons.
Keywords: E24; E32; J24; J31; J60; O33; 330; COVID-19; crisis; working from home; technological change; labor market; job mobility; digitization